Is cholecystectomy the treatment of choice for acute acalculous cholecystitis?: a systematic review of the literature - Víctor Soria-Aledo (Revista Espanola de Enfermedades Digestivas)
Background and objectives: There is currently no consensus with regard to the use of cholecystectomy or percutaneous cholecystostomy as the therapy of choice for acute acalculous cholecystitis. The goal of this study was to review the scientific evidence on the management of these patients according to clinical and radiographic findings. Methods: A systematic review of the literature from 2000 to 2016 was performed. The databases of PubMed, Índice Médico Español, Cochrane Library and Embase were searched according to the following inclusion criteria: publication language (English or Spanish), adult patients, acalculous etiology and appropriate study design. Results: A total of 1,013 articles were identified and ten articles were selected for review. These included five observational controlled studies and five case series which described the outcome of patients treated with percutaneous cholecystostomy and emergency cholecystectomy. No prospective or randomized studies were identified using the search criteria. The data from the literature and analysis of results suggested that percutaneous cholecystostomy may be a definitive therapy for acute acalculous cholecystitis with no need for subsequent elective cholecystectomy. Conclusions: Percutaneous cholecystostomy may be the first treatment option for patients with acute acalculous cholecystitis except in cases with a perforation or gallbladder gangrene. Patients at low surgical risk may benefit from cholecystectomy but both treatment options may be effective. Percutaneous cholecystostomy in patients with acute acalculous cholecystitis may be a definitive therapy with no need for a subsequent elective cholecystectomy. However, the overall quality of studies is low and the final recommendations should be considered with caution.